2011
DOI: 10.4061/2011/487592
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Comparing the Efficacy of Topical Ocular Application of Tacrolimus and Cyclosporine in Dogs

Abstract: The purpose of this paper was to determine the efficacy and safety of topical tacrolimus, compared to cyclosporine, for treating keratoconjunctivitis sicca (KCS) in dogs. This study was a two-phase, randomized, controlled, masked clinical trial. Phase 1 evaluated ophthalmic 0.03% tacrolimus in normal dogs. Ocular examinations were performed daily. Phase 2 evaluated the efficacy of tacrolimus in treating KCS. Half the dogs received 2% cyclosporine A; the others received 0.03% tacrolimus, both diluted in ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 17 publications
5
34
3
1
Order By: Relevance
“…In the present study, an increase in STT results was observed both for cyclosporine and tacrolimus. Similarly, in the research by Hendrix et al (2011), increased STT values were reported in both a group of dogs receiving 0.03% tacrolimus eye drops and a group receiving 2% cyclosporine, without statistically significant discrepancies between the two. A greater increase in STT values was observed after administering 1% pimecrolimus when compared to 0.2% cyclosporine (Ofri et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, an increase in STT results was observed both for cyclosporine and tacrolimus. Similarly, in the research by Hendrix et al (2011), increased STT values were reported in both a group of dogs receiving 0.03% tacrolimus eye drops and a group receiving 2% cyclosporine, without statistically significant discrepancies between the two. A greater increase in STT values was observed after administering 1% pimecrolimus when compared to 0.2% cyclosporine (Ofri et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
“…The authors found that tacrolimus was potentially successful in increasing tear production in dogs that were nonresponsive to CsA. 24 The limitations of our study included the small sample size and the lack of a control group, masking, and randomization.…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study suggest that a 0.3% solution of NTX given topically once daily is not effective in increasing tear production or corneal sensitivity in dogs with uncontrolled KCS. Mainstay treatments of KCS have included use of immunomodulatory/lacrimogenic drugs such as cyclosporine and tacrolimus . Recently, another drug in a similar class has been described .…”
Section: Discussionmentioning
confidence: 99%